The Wiley-Blackwell handbook of adulthood and aging - Whitbourne, Susan Krauss; Sliwinski, Martin J. (Malden, Mass. : Wiley-Blackwell, 2012)
This exceptional collection draws on the most recent demographic data and combines classic research with cutting-edge approaches to provide an invaluable overview of the developmental psychology of the adult years. Covers a wide range of topics within adult development and aging, from theoretical perspectives to specific content areasIncludes newly commissioned essays from the top researchers in the fieldTakes a biopsychosocial perspective, covering the biological, psychological and social changes that occur in adulthood.
pt. 1. Foundations -- pt. 2. Physical changes and health -- pt. 3. Cognition -- pt. 4. Personality -- pt. 5. Abnormal aging -- pt. 6. Social processes -- pt. 7. Well-being and creativity.
Includes bibliographical references and indexes.
Print version record.
Keywords: Aging -- Handbooks, manuals, etc; Adulthood -- Handbooks, manuals, etc; Gerontology -- Handbooks, manuals, etc; FAMILY & RELATIONSHIPS -- Aging; SOCIAL SCIENCE -- Gerontology; Adulthood; Aging; Gerontology; Alterspsychologie; Aufsatzsammlung; Alterspsychologie; Aufsatzsammlung; Electronic books; Handbooks and manuals